Impact of Physical Health Status of Antenatal Mothers on their Neonates - Kachapati, Anuja; Gupta, Badri Kumar (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Newborn health is closely related to that of their mothers. The simple indicators of the mother like haemoglobin level, height, weight, gestational age of the mother will give the first hand information of deviated health of the neonates. MATERIAL AND METHODS: Descriptive correlation study was conducted to assess the impact of physical health status of antenatal mothers on their neonates, 170 antenatal mothers and their born neonates were selected by using purposive sampling. Semi-structured interview schedule, observation of record review and measurement of physical health parameters were used for data collection. A descriptive and inferential statistics were used to investigate the relationships between the variables of antenatal mothers with their neonates with SPSS software version 16. RESULTS: The study findings revealed that the weight of the neonates has statistically significant correlation with the maternal weight, height, hemoglobin and maternal gestational weeks; length of the neonates has statistically significant correlation with the maternal height, maternal weight and maternal age; Gestational age (Ballard score) with the maternal gestational weeks and neonates birth weight; neonates head circumference has statistically significant with the maternal height, gestational weeks and maternal weight; chest circumference of the neonates has statistically significant with the maternal height and maternal weight. CONCLUSION: The study concluded that there was a significant correlation between the selected maternal weight, height, hemoglobin and gestational weeks with neonatal weight; maternal height, weight, age with neonatal length, head circumference, chest circumference and maternal gestational weeks with neonate gestation age by Ballard score.